2020
DOI: 10.3390/gidisord2010003
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gastric Electrical Stimulation in the Treatment of Gastroparesis

Abstract: Introduction: Gastric electrical stimulation (GES) is a surgically implanted treatment option for drug refractory gastroparesis syndromes. Evidence supporting use of GES and the pathophysiology of gastroparesis syndromes is not widely known. We conducted a descriptive review to elucidate the pathophysiology of gastroparesis syndromes, with particular focus on gastrointestinal neuromodulation and the known mechanisms of action of GES. Methods: A descriptive review of PubMed, Web of Science and Cochrane Library … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…GCSI scale was used to analyze the improvement of nausea and vomiting scores, showing that nausea scores dropped from 3.5 at baseline to 1.7 and 2.6 and six weeks and six months, respectively. Similarly, vomiting scores had dropped from 2.4 to 0.6 and 1.8 as published in a review made by Shine et al [ 18 ].…”
Section: Reviewmentioning
confidence: 79%
See 4 more Smart Citations
“…GCSI scale was used to analyze the improvement of nausea and vomiting scores, showing that nausea scores dropped from 3.5 at baseline to 1.7 and 2.6 and six weeks and six months, respectively. Similarly, vomiting scores had dropped from 2.4 to 0.6 and 1.8 as published in a review made by Shine et al [ 18 ].…”
Section: Reviewmentioning
confidence: 79%
“…Nausea and vomiting are the most frequent and bothersome symptoms experienced by patients with gastroparesis. The gastric pacemaker has been shown to help alleviate these symptoms, as described in the studies in our review [ 18 ]. A study conducted between 1998 to 2009 on 50 patients revealed that there was an improvement in nausea (2.46 vs. 1.35, P =.001) and vomiting (3.35 vs. 1.49, P<0.001) [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations